Mental health components addressed in peace agreements for armed conflicts completions in the world - Concha Mendoza, Cristian Camilo; Camelo Mendoza, Rossana Ninoska (Gaceta Médica de Caracas, 2021)
It is known that there have been armed conflicts around the world that ended through a negotiated exit but ¿Have the mental health has been a central component in peace agreements for the termination of armed conflicts in different geographical areas around the world? This question will try to answered through a systematic review of representative conflicts around the world with a qualitative methodology. Se sabe que ha habido conflictos armados en todo e lmundo que terminaron con una salida negociada pero ¿la salud mental ha sido un componente central en los acuerdos de paz para la terminación de los conflictos armados en diferentes áreas geográficas del mundo?